Before-School Running/Walking Club and Student Physical Activity Levels: An Efficacy Study. Issue 4 (1st October 2016) - Stylianou, Michalis; van der Mars, Hans; Kulinna, Pamela Hodges; Adams, Marc A.; Mahar, Matthew; Amazeen, Eric
Abstract : Purpose: Before-school programs, one of the least studied student-related comprehensive school physical activity program (CSPAP) components, may be a promising strategy to help youth meet the physical activity (PA) guidelines. This study's purpose was to examine: (a) how much PA children accrued during a before-school running/walking club and during the school day, (b) whether children compensated for the PA accumulated in the before-school program by decreasing their school-day PA, and (c) potential sex and body mass index (BMI) differences.Method: An alternating treatments design with a baseline phase was first conducted at a private school (School A) and was subsequently replicated at a public school (School B). Participants ( N  = 88) were 3rd- and 4th-grade children. The before-school program involved a running/walking club that met twice per week (School A: 20 min; School B: 15 min). PA was measured using the NL-1000 pedometer. Data analysis included multilevel modeling and visual analysis.Results: Children accumulated substantial amounts of PA in the before-school programs (School A: 1, 731 steps, 10:02 moderate-to-vigorous PA minutes or 50% of program duration; School B: 1, 502 steps, 8:30 moderate-to-vigorous PA minutes or 57% of program duration). Additionally, children did not compensate by decreasing their school-day PA on days they attended the before-school program. Sex differences were found in before-school program PA only for School B and in school-day PA for both schools. No BMI differences were found.Conclusions: Before-school programs, as part of CSPAPs, can help children increase their PA without resulting in decreased school-day PA and without taking time away from academics.